Saline infusion sonography in evaluation of uterine cavity abnormalities in infertility: a comparative study - Sitimani, Anita; Chawla, Indu; Vohra, Poonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Infertility is defined as one year of unprotected intercourse without pregnancy. Female factor is responsible for 40-50% of cases of infertility. Uterine pathologies are the cause of infertility in as many as 15% of couples seeking treatment. The objective of this study was to evaluate the accuracy of trans-vaginal sonography (TVS) and saline infusion sonography (SIS) for detection of uterine cavity abnormalities in patients of infertility taking hysteroscopy as gold standard. Methods: A prospective comparative study was done in 60 patients of infertility. Patients were selected from gynaecology OPD of a tertiary care hospital. Patient selected underwent TVS and SIS followed by hysteroscopy for presence of uterine cavity abnormalities. The presence of uterine cavity abnormality and its type (endometrial polyp, submucous myoma, intrauterine synechiae or any other) was noted. The results of TVS and SIS were compared with hysteroscopy. Results: In 60 infertile patients, hysteroscopy revealed intrauterine pathology in 22 patients (36.7%). Among them eight had endometrial polyp and another eight patients had intrauterine synechiae. Submucous myoma was detected in five patients and one patient had thin endometrium. SIS detected eight out of 22 uterine cavity abnormalities indicating sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of 36.4%, 100%, 100% and 73.1% respectively. In comparison TVS showed abnormalities in six patients only and thus had sensitivity, specificity, PPV and NPV of 27.35%, 100%, 100% and 70.4 % respectively. Sensitivity of SIS for specific lesion was least for intrauterine synechiae (12.5%) and maximum for submucous myoma (60%). Conclusions: The sensitivity of both TVS and SIS for detection of uterine cavity abnormalities in patients of infertility was low in the present study and they cannot be recommended as replacement for hysteroscopy.